Accumulation of chlorpyrifos on residential surfaces and toys accessible to children. - Gurunathan, S (1998)
Quantitative examination of major pathways and routes of exposure to pesticides is essential for determining human risk. The current study was conducted in two apartments and examines the accumulation of the pesticide chlorpyrifos in childrens' toys after the time suggested for reentry after application. It has been established for the first time that a semivolatile pesticide will accumulate on and in toys and other sorbant surfaces in a home via a two-phase physical process that continues for at least 2 weeks postapplication. A summation of the above for a 3-6-year-old child yielded an estimated nondietary total dose of 208 microg/kg/day. Potential exposure from the inhalation pathway was negligible, while dermal and nondietary oral doses from playing with toys contributed to 39 and 61% of the total dose, respectively. If children with high frequency mouthing behavior are considered as candidates for acute exposure to chlorpyrifos residues, the estimated acute dose could be as high as 356 microg/kg/day. Routine reapplication of pesticides could lead to continued accumulation in toys and other sorbant surfaces, e.g., pillows, with large sorbant reservoirs, which can become a long-term source of exposure to a child. Estimates of a child's nondietary exposure to chlorpyrifos associated with toys and other sorbant surfaces for a period of 1 week following application appear to be of public health concern, and studies of actual childhood exposure from this pathway are warranted in the home environment. The above information should be used to determine if current procedures for postapplication reentry are sufficient and to evaluate the need for procedures to store frequently used household toys, pillows, and other sorbant objects during insecticidal application.